2006
DOI: 10.1103/physrevlett.97.165301
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Classical Rotational Inertia and Nonclassical Supersolid Signals in SolidHe4below 250 mK

Abstract: We have confirmed the existence, as first reported by Kim and Chan, of a supersolid state in solid 4 He at temperatures below 250 mK. We have employed a torsional oscillator cell with a square cross section to insure a locking of the solid to the oscillating cell. We find that NCRI signal is not a universal property of solid 4 He, but can be eliminated through an annealing of the solid helium sample. This result has important implications for our understanding of the supersolid state. He confined within the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

36
309
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(346 citation statements)
references
References 8 publications
36
309
1
Order By: Relevance
“…The T clean c < 0 scenario is supported by recent experiments [14], showing non-classical rotational inertia in unannealed 4 He crystals, but none after annealing. On the other hand, Chan's recent experiments [11], as discussed above and in figure (2), suggest T clean c > 0.…”
supporting
confidence: 64%
“…The T clean c < 0 scenario is supported by recent experiments [14], showing non-classical rotational inertia in unannealed 4 He crystals, but none after annealing. On the other hand, Chan's recent experiments [11], as discussed above and in figure (2), suggest T clean c > 0.…”
supporting
confidence: 64%
“…The discovery of a non-classical rotational inertia fraction (NCRIF) in solid 4 He by Kim and Chan [1,2] has generated enormous interest because the NCRIF could be the signature of a supersolid state [3]. Several independent experiments [4,5] have shown that the NCRIF magnitude and temperature dependence are strongly dependent on defects such as 3 He impurities and the quality of the crystals. Recently studies of the elastic properties of solid 4 He by Beamish and colleagues [6] have revealed a significant frequency dependent change in the elastic shear modulus with an enhanced dissipation peak having a temperature dependence comparable to that observed for the NCRIF.…”
mentioning
confidence: 99%
“…Following the discovery by Kim and Chan (KC) [1, 2] of the supersolid or nonclassical rotational inertia (NCRI) state of bulk solid 4 He, several independent groups using the same torsional oscillator technique have confirmed the KC supersolid results. These include the Japanese groups of Shirahama et al [3], working at Keio University, and Kubota et al [4] at the ISSP, as well as our group [5] at Cornell University. In these early experiments, the solid samples were formed by the blocked capillary technique.…”
mentioning
confidence: 99%
“…These include the Japanese groups of Shirahama et al [3], working at Keio University, and Kubota et al [4] at the ISSP, as well as our group [5] at Cornell University. In these early experiments, the solid samples were formed by the blocked capillary technique.…”
mentioning
confidence: 99%